Grafting density-induced smectic A to hexagonal columnar transition in mesogen-free isotactic liquid crystalline polyethers with n-dodecylsulfonyl side groups. (March 2020) - Kwok, Man-Hin; Bohannon, Caleb A.; Crooks, Jordan L.; Li, Ruipeng; Zhao, Bin; Zhu, Lei
Abstract: Highly dipolar mesogen-free liquid crystalline polymers are excellent candidates for achieving large spontaneous polarization under relatively low electric fields for advanced electrical and optical applications. In this report, the effect of grafting density of n -dodecylsulfonyl side chains on the mesogen-free liquid crystalline self-assembly of comb-like isotactic poly(oxypropylene) was studied. When the grafting density was 80–100%, a stable 21 helical chain conformation was induced by the strong dipole-dipole interactions among the sulfonyl groups in the side chains. Consequently, a smectic A self-assembly was induced. When the grafting density decreased to 60–80%, a poor and possibly imbalanced 21 helical chain conformation was formed due to the frequent absence of the n -dodecylsulfonyl side chains along the main chain. As a result, a hexagonal columnar self-assembly was realized. This study demonstrated that a delicate interplay between the molecular defects and dipole-dipole interactions can lead to different self-assembly structures. Graphical abstract: Image, graphical abstract